FP-LAPW Study of Phase Changesin An(A = Al,IN, and B) Under High Pressure - Haneen Yousef Saeed Shalash (My University, 2009)
In the last few years no other class of material of semiconductors has attracted so much scientific and commercial attention like the group III-nitrides( AlN, BN, and InN). The increasing interest is due to its extraordinary physical properties, which can be used in many new electronic and optoelectronic devices. The AlN is stable to very high temperatures in inert atmospheres. Another stable material in inert and reducing atmospheres is BN. It is a very good electrical insulator. It offers very high thermal conductivity and good thermal shock resistance. In N has attracted considerable attention due to the repeated observation of an effective band gap in the range around 0.7 eV by optical techniques, this smaller band gap value would extend the possible emission range of optoelectronic devices based on III-nitrides from the deep-UV down to the near-IR region. Very prominent examples are the short wavelength Light emitting diodes (LED’s) and laser diodes, which take advantage of the wide band gap of AlN. InN also has been expected to be a suitable material for electronic devices such as high mobility transistors due to its small effective mass. The effect of pressure on the electronic properties of (AlN, BN, and InN) are  investigated using both experimental and theoretical methods. In this study, we carry out all-electron full potential linearized-augmented plane waves (FP-LAPW) (which is included in a computer code WIEN2K) approach within the density functional theory (DFT) in the local density approximation (LDA), and the generalized gradient approximation (GGA) for the exchange correlations functional, which used to calculate ground-state energies, the lattice parameters, the bulk modulus and its derivatives, transition pressure and the band structures. The equation of state of wurtzite (WZ), zincblende(ZB) and rocksalt(RS) structures for (AlN, BN, and InN) compounds have been calculated.  In this study, the most important results are: 1.The present calculations agree very well with available experimental data and other theoretical calculations. 2.AlN compound behaves as an insulator in (WZ, ZB, and RS) structures. 3.BN compound behaves as a semiconductor for RS and ZB in LDA calculation and an insulator for RS and ZB in GGA calculation. 4.InN compound behaves as a semimetal in (WZ, ZB, and RS) structures. 5.The energy band gap for (WZ, RS, and ZB ) structures of AlN are found to be (4.42, 4.032, 2.7) eV respectively,  using  LDA method, and (4.17, 4.34, 3.275) eV respectively, using GGA method. 6.The energy band gap for (ZB and RS) structures of BN are found to be (4.36, 2.193) eV respectively, using LDA method, and (4.43, 1.71) eV respectively, using GGA method. 7.The energy band gap for (WZ, RS, and ZB ) structures of InN are found to be ( -0.264, 0.0838, -0.3896) eV respectively, using  LDA method, and (-0.3643, -0.277, -0.5136) eV respectively, using GGA method. 8.For AlN the transition pressure from wurtzite to rocksalt was found to be (10) GPa and from zincblende to rocksalt was found to be (4.64) GPa using GGA method, while the transition pressure from wurtzite to rocksalt was found to be 9.3 GPa and from zincblende to rocksalt was found to be 3 GPa using LDA method. 9.For InN the transition pressure from wurtzite to rocksalt was found to be 16.6 GPa and from zincblende to rocksalt was found to be 18.5 GPa using GGA method. 10.The transition pressure for BN compound from zincblende to rocksalt was found to be 500 GPa using GGA method.

في السنوات السابقة لم يلفت الأنتباه نوع أخر من مواد أشباه الموصلات علميا وتجاريا مثلما لفتت الأنتباه مجموعة النتريدات الثلاثة IN)و BN و InN) ويرجع سبب هذا الاهتمام المتزايد إلى الخصائص الفيزيائية غير العادية التي تتميز بها هذه المجموعة والتي يمكن استخدامها في العديد من الابتكارات الالكترونية والالكترونات البصرية ومن الأمثلة الظاهرة على ذلك صمامات الليزر ذات الموجه القصيرة والتي تستفيد من الفجوة العريضة لأحد مكونات هذه المجموعة وهو .AIN كما أن مركب InN كان من المتوقع أن يكون مادة مناسبة للابتكارات الالكترونية مثل ترانزستورات ذات انتقالية عالية نتيجة لكتلته الفاعلة. إن اعتماد التألق الضوئي على الضغط يعتبر مهم جدا في فهم الطاقة الالكترونية والخواص التركيبية والمكونات الصلبة في أشباه الموصلات. إن اثر الضغط على الخواص الالكترونية للمواد (AIN و BNوInN) يمكن استقصاؤه باستخدام كلا الطريقتين التجريبية والنظرية. في هذه الأطروحة تم الاعتماد على أسلوب الجهد المزيد والتام ذو الموجات المستوية الخطية والذي يعمل تحت برنامج حاسوب يسمى (WIEN2K) والذي يعتمد على نظرية كثافة الشحنات داخل الذرات حيث يستخدم فيها أسلوبين للتقريب وهما LDA)) و (GGA) في تحديد مستويات الطاقةالمستقرة.
دراسة تغيرات الحالة لكل من المركبين نترات الالمنيوم ونترات الانديوم تحت ضغط عال باستخدام طريقة FP-LAPW